Drug use by school adolescents and associated factors - da Silva, Felicialle Pereira (2024)
Objective: to analyze the association between family, sexual and violence variables and drug use in the last month by adolescents. Method: this is a cross-sectional study, conducted with 147 students enrolled in a reference high school in the state education system of the state of Pernambuco. Students aged between 15 and 19 years participated. A sociodemographic questionnaire and part I of the Drug Use Screening Inventory, which deals with drug use in the last month, were used to collect data. Data analysis was performed and presented in univariate and bivariate forms. Results: the results revealed an association between experiencing violence, having family members who use drugs, having sexual intercourse and using or not using condoms during sexual intercourse, and drug use in the last month by adolescents. Conclusion: drug use in the last month by adolescent students is influenced by experiences of violence, drug use by family members, sexual intercourse and having these relations with or without the use of condoms.